2016
DOI: 10.1017/s1751731115002037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scalding and dehairing of pig carcasses at abattoirs on the visibility of welfare-related lesions

Abstract: There is increasing interest in developing abattoir-based measures to assist in determining the welfare status of pigs. The primary aim of this study was to determine the most appropriate place on the slaughter line to conduct assessments of welfare-related lesions, namely apparent aggression-related skin lesions (hereafter referred to as 'skin lesions'), loin bruising and apparent tail biting damage. The study also lent itself to an assessment of the prevalence of these lesions, and the extent to which they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 27 publications
4
47
4
1
Order By: Relevance
“…Thus, weaning of smaller pigs could lead to more challenges in the grower-finisher period and influence the risk of tail biting. A higher prevalence of tail lesions in a batch is also associated with a lower average cold carcass weight (Carroll et al, 2015). Similarly, we found that as the percentage of severe tail lesions increased the average live weight at which finisher pigs were sold decreased.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, weaning of smaller pigs could lead to more challenges in the grower-finisher period and influence the risk of tail biting. A higher prevalence of tail lesions in a batch is also associated with a lower average cold carcass weight (Carroll et al, 2015). Similarly, we found that as the percentage of severe tail lesions increased the average live weight at which finisher pigs were sold decreased.…”
Section: Discussionsupporting
confidence: 72%
“…Harley et al performed two studies of slaughter pigs in abattoirs in the Republic of Ireland and Northern Ireland and found that 60% to 70% of the observed slaughter pigs had detectable tail lesions on the carcass (Harley et al, 2012b and. Tail lesions are more visible on the carcass, especially less severe bite marks, compared with the live animal suggesting that recording tail lesions during meat inspection is more accurate (Velarde et al, 2005;Harley et al, 2012a;Carroll et al, 2015;van Staaveren et al, 2015). An undocked, uninjured tail at slaughter is considered a gold standard for pig welfare and suggested as an 'iceberg indicator' capable of providing an overall picture of the health/ welfare of pigs (Farm Animal Welfare Council (FAWC), 2009; European Food Safety Authority (EFSA), 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of this project was to incorporate health and welfare indicators in the MI process. The advantages of assessing pig health and welfare at MI have previously been described, ranging from a large amount of data collection, higher visibility of certain conditions, reduced risk to biosecurity and disease transmission compared to on-farm assessments [6,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participants did not prioritize welfare indicators (e.g., bursitis, tail lesions, abscesses) as they believed they would be visible on-farm, despite the fact that previous research showed increased visibility when recording these welfare lesions at MI [16]. Moreover, MI was considered to offer the opportunity to record "invisible" health indicators at MI, i.e., those that could not be observed on-farm, contributing to the emphasis on health indicators.…”
Section: Health and Welfare Indicatorsmentioning
confidence: 94%
“…Stakeholders attributed this ease to the relative absence of time constraints and better visibility of the pigs, although in reality this is not often the case [24]. However, while there is value in data collected at ante-mortem particularly relating to animals requiring special attention (or casualty animals), the key information on the health and welfare of the herd must be gleaned from the carcass and viscera post mortem (i.e., at MI) [4].…”
Section: Discussionmentioning
confidence: 99%